A fast method for the psychophysical estimation of nonlinear cochlear function using schroeder-phase masking - Rahmat, Sarah; O'Beirne, Greg A. (ibrahim KARA, 2015)
The power spectrum model of masking (Patterson and Moore, 1986) assumes that the masking ability of a sound is affected only by the frequency and intensity of the masker, but not the phase. The well-documented difference in masking produced by different phases of Schroeder- phase harmonic complexes the ("phase effect") is thought to be contributed by the phase curvature of the auditory filter and nonlinear cochlear processing (Kohlrausch & Sander, 1995). We have recently developed a fast method for recording Schroeder-phase masking functions in humans which takes 8 minutes of testing time rather than the 45 minutes taken by the conventional three alternative forced choice (3AFC) method. We demonstrate here the reliability of this new method and its potential use in measuring cochlear non-linearity. Schroeder-phase masking functions were measured in 38 normal hearing and 15 hearing impaired participants using the conventional and fast methods. Results from our fast method agreed well with those from the conventional 3AFC method. We also used the fast method to measure functions at 0.25, 0.5, 1, 2, and 4 kHz at 45 and 75 dB A masker levels in normal hearing and hearing impaired participants, and found significantly reduced phase effects at low presentation levels and in participants with SNHL compared to normal hearing participants (p<0.05), consistent with reductions in cochlear nonlinearity in those conditions. With an 80% reduction of testing time as compared to the conventional method, the fast method has great potential to aid future studies estimating nonlinear cochlear function.